1967
DOI: 10.1207/s15327906mbr0203_2
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Structure Of Social Attitudes And Personality : A Multidimensional Scaling Approach

Abstract: This study examined the relationships between attitudes inferred from behavior and attitudes implied by item content. 60 subjects judged the similarity between all possible pairs of 18 attitude items and 6 person descriptions designed to reflect three hypothesized dimensions of authoritarian ideology. These interstimulus similarity judgments were subjected t o a multidimensional scaling analysis. Results supported the hypotheses that (a) subsets of attitude statements reflecting hypothesized facets of authorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Thsi, was mitigated by the somewhat exploratory nature of the study. (Boyd & Jackson, 1967, also scaled people and statements in the same MDS space, but their "people" were hypothetical behavioral descniptions designed to correspond to the statements, which were taken from the F scale.) In future applimtions of this methodology, suoh conservatism need not be followed.…”
Section: Discussionmentioning
confidence: 99%
“…Thsi, was mitigated by the somewhat exploratory nature of the study. (Boyd & Jackson, 1967, also scaled people and statements in the same MDS space, but their "people" were hypothetical behavioral descniptions designed to correspond to the statements, which were taken from the F scale.) In future applimtions of this methodology, suoh conservatism need not be followed.…”
Section: Discussionmentioning
confidence: 99%
“…Using attitudes toward war, capital punishment, and treatment of criminals, he found that (1) the perceived relationships could be adequately represented in dimensional terms, and (2) the configuration of seminary students and Air Force officer candidates were almost identical. Boyd and Jackson (1967) investigated attitudes designed to reflect three hypothesized dimensions of authoritarian ideology. Using interstimulus similarity judgments and multidimensional scaling, they found that subsets of attitude statements reflecting the hypothesized facets were perceived as representing independent dimensions.…”
mentioning
confidence: 99%
“…They are distinguishable by class. Recent research (Boyd and Jackson, 1967) shows that different classes of social objects can be included within a single domain.…”
Section: Addendum To Chapters I and Iimentioning
confidence: 99%